Prediction of major adverse kidney events in critically ill burn patients. Issue 8 (December 2018) - Dépret, François; Boutin, Louis; Jarkovský, Jiří; Chaussard, Maité; Soussi, Sabri; Bataille, Aurélien; Oueslati, Haikel; Moreno, Nabila; de Tymowski, Christian; Parenica, Jiří; Benešová, Klára; Vauchel, Thomas; et al.
Highlights: pNGAL at admission is a good predictor of severe AKI. The biomarker is strongly associated with the risk of MAKE in this population. pNGAL when added to clinical severity score, outperforms severity scores alone. Abstract: Objective: We aimed at assessing the predictive value of plasmatic Neutrophil Gelatinase Associated Lipocalin (pNGAL) at admission and severity scores to predict major adverse kidney events (MAKE, defined as death and/or need for renal replacement therapy (RRT) and/or non-renal recovery at day 90) in critically ill burn patients. Material and methods: Single-center cohort study in a burn critical care unit in a tertiary center, including all consecutive severely burn patients (total burned body surface >20%) from January 2012 until January 2015 with a pNGAL dosage at admission. Reclassification of patients was assessed by Integrated Discrimination Improvement (IDI). Measurements and results: 87 patients were included. Mean age was 47.7 (IQ 25–75: 33.4–65.2) years; total burn body surface area was 40 (IQ 25–75: 30–55) % and ICU mortality 36%. 39 (44.8%) patients presented a MAKE, 32 (88.9%) patients died at day 90. pNGAL was higher in the MAKE group (423 [IQ 25–75: 327–518] pg/mL vs 184 [IQ 25–75: 147–220] pg/mL, p < 0.001). In multivariate analysis, pNGAL and abbreviated burn severity index (ABSI) remained associated with MAKE (OR 1.005 [CI 95% 1.0005–1.009], p = 0.03 and OR 1.682 [CI95%1.038–2.726], p = 0.035 respectively). Adding pNGAL to abbreviated burn severity index, simplified organ failure assessment and the simplified acute physiology score 2 did outperform clinical scores for the prediction of MAKE and AKI and for most severe forms of AKI and allowed a statistically significant reclassification of patients compared to ABSI for MAKE, RRT, AKI at Day 7 and AKI during hospitalization with a number of patients needed to screen to detect one extra episode of MAKE was 44, 13 for severe AKI and 15 for AKI. Conclusions: pNGAL at admission is associated with the risk of MAKE in this population, and outperform severity scores when associated. Interventional studies are now needed to assess if impact of biomarkers-guided strategies would improve outcome.